Ответ:
а) 3
б) 0,5
в)0
г)0
Объяснение:
а)
б)
в)
г)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
а) 3
б) 0,5
в)0
г)0
Объяснение:
а)![(3x-1)(5x+4)-15x^2=17\\15x^2+12x-5x-4-15x^2=17\\7x=17+4\\7x=21\\x=3 (3x-1)(5x+4)-15x^2=17\\15x^2+12x-5x-4-15x^2=17\\7x=17+4\\7x=21\\x=3](https://tex.z-dn.net/?f=%283x-1%29%285x%2B4%29-15x%5E2%3D17%5C%5C15x%5E2%2B12x-5x-4-15x%5E2%3D17%5C%5C7x%3D17%2B4%5C%5C7x%3D21%5C%5Cx%3D3)
б)![(1 - 2x)(1 - 3x) = (6x - 1)x - 1\\1-3x-2x+6x^2=6x^2-x-1\\-5x+6x^2-6x^2+x=-1-1\\-4x=-2\\4x=2\\x=0,5 (1 - 2x)(1 - 3x) = (6x - 1)x - 1\\1-3x-2x+6x^2=6x^2-x-1\\-5x+6x^2-6x^2+x=-1-1\\-4x=-2\\4x=2\\x=0,5](https://tex.z-dn.net/?f=%281%20-%202x%29%281%20-%203x%29%20%3D%20%286x%20-%201%29x%20-%201%5C%5C1-3x-2x%2B6x%5E2%3D6x%5E2-x-1%5C%5C-5x%2B6x%5E2-6x%5E2%2Bx%3D-1-1%5C%5C-4x%3D-2%5C%5C4x%3D2%5C%5Cx%3D0%2C5)
в)![12-x(x-3)=(6-x)(x+2)\\12-x^2-3x=6x+12-x^2-2x\\-x^2-3x-6x+x^2+2x=12-12\\-7x=0\\x=0 12-x(x-3)=(6-x)(x+2)\\12-x^2-3x=6x+12-x^2-2x\\-x^2-3x-6x+x^2+2x=12-12\\-7x=0\\x=0](https://tex.z-dn.net/?f=12-x%28x-3%29%3D%286-x%29%28x%2B2%29%5C%5C12-x%5E2-3x%3D6x%2B12-x%5E2-2x%5C%5C-x%5E2-3x-6x%2Bx%5E2%2B2x%3D12-12%5C%5C-7x%3D0%5C%5Cx%3D0)
г)![(x+4)(x+1)=x-(x-2)(2-x)\\x^2+x+4x+4=x-2x+x^2+4-2x\\x^2+5x-x^2+3x=4-4\\8x=0\\x=0 (x+4)(x+1)=x-(x-2)(2-x)\\x^2+x+4x+4=x-2x+x^2+4-2x\\x^2+5x-x^2+3x=4-4\\8x=0\\x=0](https://tex.z-dn.net/?f=%28x%2B4%29%28x%2B1%29%3Dx-%28x-2%29%282-x%29%5C%5Cx%5E2%2Bx%2B4x%2B4%3Dx-2x%2Bx%5E2%2B4-2x%5C%5Cx%5E2%2B5x-x%5E2%2B3x%3D4-4%5C%5C8x%3D0%5C%5Cx%3D0)